PENGARUH BEBAN KERJA, STRES KERJA DAN LINGKUNGAN KERJA NON FISIK TERHADAP INTENSI KELUAR PADA KARYAWAN PT BPR BANK BAPAS 69 MAGELANG - Lathif, Muhammad Zaki; Achsa, Andhatu; Ikhwan, Khairul (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
The desire of employees to leave their jobs does not only have an impact on the employees themselves, but also has an impact on the company. Hence, it is necessary to find out whether workload, work stress, non-physical work environment affect employee intention to leave. This research was conducted at PT BPR Bank BAPAS 69 Magelang with 225 employees as respondents using a random sampling technique of 144. Interviews and questionnaires were used to collect data, and SPSS was used to analyze data using multiple linear regression techniques. According to the findings, the variables of workload and stress at work have a significant impact on intention to quit work. Variables related to non-physical work environment had no discernible impact on intention to leave. At PD BPR Bank Bapas 69, Magelang Regency, the three independent variables simultaneously have a considerable influence on the intention to leave.